ISLAMIC PARENTING PATTERNS BASED ON GENDER EQUALITY IN GENERATION Z PARENTS - Rizky Hanifah; Yogi Sopian Haris; Anisa Fauziah Apriani; Windila Santoso; Khalisha Awliya Berutu (Adisam Publisher, 2025)
Parenting encompasses is all interactions applied by parents in guiding and educating children to ensure they grow and develop well. Generation Z is a generation that grew alongside the development of technology, making them more openminded to various information. They have a different parenting style from the previous generation, which tended to adhere patriarchal principles. The researchers chose Gen Z as the research subject on Islamic parenting based on gender equality due to the differences parenting styles from previous. Gen Z entering parenthood moment now, so it can be new topic for research. This research uses a qualitative approach. The research results show that Generation Z parents have thoughts aligned with gender-equal Islamic parenting. However, the realization of that aspect has not yet been fully implemented by them. This shows that Gen Z, when they become parents, start to realize the importance of raising children without considering a specific gender.